ANALISIS KEBIJAKAN ALBA & PETROCARIBE NICOLAS MADURO MOROS UNTUK MENGHADAPI DOMINASI POLITIK NEOLIBERALISME AMERIKA SERIKAT DI VENEZUELA PADA TAHUN 2015 - 2017 - Laode Muhamad Fathun (Indonesian Journal of Peace and Security Studies (IJPSS), 2020)
Poverty in this country. During the reign of Chavez and Maduro the people felt a little prosperity again, but this is what America hates because America is finding it difficult to implement its neoliberalism policy in Venezuela. After the events that continue to happen, Maduro does not remain silent. Namely by continuing Chavez's socialist policies. Here the researcher uses the theory of foreign policy decision making by Alex Mintz to explain what factors influence Maduro policy and here the researcher uses the concept of national interest to explain what Maduro's interests are in this policy, this research methodology is qualitative explanatory using interviews as data. secondary and librarian as primary data. This research finds 4 main factors in Nicolas Maduro's foreign policy. From the social condition of Venezuela itself which is very crisis-ridden to the point where there is a split between the layers of society, Maduro finally does not listen to the people's complaints to him, then from a psychological point of view, Maduro, who really hates the United States, has a very tough mindset that he is too confident in his beliefs. In order to be able to fight America, in the end his belief was not in accordance with expectations and instead had a negative effect. Therefore, it is clear that emotions play an important role in important political decisions. From an economic point of view, Venezuela is no longer able to support its own country in economic terms. If this country supports itself, there will be greater destruction